Análise numérica de barras compostas em perfis de aço formados a frio submetidas à compressão - Nunes, Riterson Jacques (Universidade Federal de São Carlos, 2021)
Built-up columns are an interesting alternative when isolated channels do not comply with structural performance requirements. During their lifespan, one of the most common stresses in built-up columns is the compression. Usually, built-up columns are formed by two channels spaced apart, examples being doubled U “back-to-back” or “front to front”. The various possibilities of bracing change the structural behavior to the shear, thus make it difficult to predict the normal resistance force of compression. The American Standard ANSI/AISI S100 (2020) presents an adaptation of the global slenderness for built-up columns, but only considers profiles in contact. Eurocode 3 (2006) distinguishes in elastic analysis, battened and laced built-up columns, but without a specific calculation method for cold-formed profiles. In this context, this work has as main objective to analyze the axial compression resistant capacity of built-up columns in double U section “back-to-back”. Numerical analyzes were carried out in the Ansys software to evaluate the influence of the following geometric parameters on structural behavior: types of bracing, number of battened plates, length of the built-up columns, spacing between channels and thickness of the channels. For each of the models, the normal compressive strength and instability modes were evaluated. In addition, the applicability of normative procedures to predict the resistive force was also evaluated. The results showed that longer built-up columns presented greater increase in the normal resistance force when compared to insulated channels. The increase in the number of battened plates did not show linear variation of the normal resistant force. For battened built-up columns, in most cases analyzed, Eurocode 3 (2006) presented lower resistance values than ANSI/AISI S100 (2020). Lot laced built-up columns Eurocode 3 (2006) underestimated the numerical results for greater thickness. The type of bracing had a greater influence on the models with higher overall slenderness, that is, for greater lengths and closer channels.
Numerical analysis of built-up columns in cold formed steel channels submitted to compression
Keywords: Barras compostas de aço; Perfis formados a frio; Compressão; Análise numérica não-linear; Instabilidades; Steel built-up columns; Cold-formed steel members; Compression; Non-linear numerical analysis; Instabilities; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS